Peningkatan Motivasi Belajar Melalui Metode Belajar Interaktif Siswa Disabilitas Intelektual di SLBN 2 Yogyakarta: Penelitian - Naza Maura Arifin; Muhammad Ridho Haekal; Dea Hanifah; Mu’adzah Fikri Nur’aini; Nur Fitriani Hardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The low learning motivation of students with intellectual disabilities is influenced by cognitive limitations, as well as instructional practices in special schools that are not yet fully adaptive. Based on these conditions, this community service program is directed at implementing instructional strategies that can enhance the learning motivation of students with intellectual disabilities through interactive learning approaches. The activities focus on hands-on implementation in the classroom to apply interactive methods directly to students with intellectual disabilities at SLBN 2 Yogyakarta. Interactive learning media were developed based on the needs of students with intellectual disabilities. The results of this program indicate that the application of interactive learning accompanied by positive reinforcement can foster more consistent learning motivation among students with intellectual disabilities. In addition, direct engagement in the field enables adjustments to methods according to each student’s needs, leading to increased enthusiasm and willingness to complete tasks. In conclusion, interactive instructional strategies tailored to the characteristics of students with intellectual disabilities play a significant role in improving learning motivation at SLBN 2 Yogyakarta.